TRATEGIES TO REDUCING PESTICIDE RESIDUES IN FOOD: REMARKS ON PESTICIDE FOOD POISONING SCENARIOS IN NIGERIA (1958 - 2018) - Koleayo, Omoyajowo; Adesuyi, Adeola Alex; Omoyajowo, Kolawole; Odipe, Oluwaseun; Ogunyebi, Lanrewaju (Journal of Agricultural Sciences (Belgrade), 2022)
Food insecurity across the globe particularly in developing countries such as Nigeria portends deleterious health challenges owing to various environmental contaminants among which are the incursion of pesticides into the biosphere and the consequential retention of pesticide residues in food composition. This study provided a depth of insights into a comprehensive analysis on how the indiscriminate applications of pesticides have distorted both the terrestrial and aquatic ecosystems, altered the food-chain and occasioned appalling incidence of food poisoning. Available data from 1958 to 2018 on pesticide food poisoning scenarios in Nigeria were collected, collated and critically evaluated. The findings of this analytical study, which is navigated through a thorough content and discourse analysis of reliable information, unveiled the various channels through which pesticides residue had penetrated into the food chain and its hazardous implications on the plants, animals and humans being at the receiving ebb of the food chain. In addressing this dilemma, the authors suggested a seam of inter-connected strategies to reduce pesticide poisoning which if adopted by the Nigerian government and that of other developing countries will effectively combat the pervasiveness of this threat to food security.